2015
DOI: 10.1001/jamaoto.2015.1451
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thyroid Nodule Size and Bethesda Class With Rate of Malignant Disease

Abstract: Our results suggest that smaller TNs (smaller than about 2.0 cm) are associated with increased probabilities of malignant disease irrespective of Bethesda class. Routine diagnostic thyroid lobectomy solely owing to TN size of 3.0 cm or greater need not be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 33 publications
5
41
1
2
Order By: Relevance
“…The authors noted that the accuracy of FNAC increased with increasing nodule size. Similarly, Magister et al [21] performed a retrospective study of 297 patients with 326 thyroid nodules, who underwent FNAB and subsequent thyroidectomy. The overall rate of malignancy on final pathology was 43.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors noted that the accuracy of FNAC increased with increasing nodule size. Similarly, Magister et al [21] performed a retrospective study of 297 patients with 326 thyroid nodules, who underwent FNAB and subsequent thyroidectomy. The overall rate of malignancy on final pathology was 43.9%.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in false negative rates with large thyroid nodules is thought to be due to sampling error. On the other hand, several authors have demonstrated low false negative rates in large thyroid nodules, similar to those in small thyroid nodules [1718192021]. …”
Section: Introductionmentioning
confidence: 99%
“…A classification based on ultrasound reporting and data system (Thyroid Imaging Reporting and Data System [TIRADS]) has been shown to be useful in stratifying the risk of malignancy of thyroid nodule . Nodule size, however, was not included among predictive ultrasound features because data are not consistent among different authors . Discrepancies can be explained by differences in experimental design, sample size, genetic background, levels of iodine intake, and patients' selection among studies.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive values of benign cytology following fine‐needle aspirations (FNA) in large thyroid nodules vary significantly between reports. The majority of authors have found FNA of large nodules to be reliable, with false negatives (FN) ranging from 0.7% to 7% . Others have found FN rates substantially higher when compared to smaller thyroid nodules …”
Section: Introductionmentioning
confidence: 99%